2002
DOI: 10.1095/biolreprod66.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Occurrence of Late-Gestation Losses from Cattle Cloned Embryos

Abstract: Nuclear transfer from somatic cells still has limited efficiency in terms of live calves born due to high fetal loss after transfer. In this study, we addressed the type of donor cells used for cloning in in vivo development. We used a combination of repeated ultrasonography and maternal pregnancy serum protein (PSP60) assays to monitor the evolution of pregnancy after somatic cloning in order to detect the occurrence of late-gestation losses and their frequency, compared with embryo cloning or in vitro fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
225
4
34

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(278 citation statements)
references
References 32 publications
9
225
4
34
Order By: Relevance
“…The causes of abortion remain unclear, although incomplete genetic reprogramming or abnormal gene expression of nuclear transfer embryos may contribute to high abortion rates after embryo transfer (Saikhun et al, 2004). Incidence of loss between day 90 of gestation and calving was 43.7% for bovine adult somatic clones (Heyman et al, 2002), which was much lower than those encountered in the current study. Serum starvation may often result in reduced cell survival and increased DNA fragmentation, which in turn cause subsequent high embryonic loss after nuclear transfer (Shi et al, 2007).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The causes of abortion remain unclear, although incomplete genetic reprogramming or abnormal gene expression of nuclear transfer embryos may contribute to high abortion rates after embryo transfer (Saikhun et al, 2004). Incidence of loss between day 90 of gestation and calving was 43.7% for bovine adult somatic clones (Heyman et al, 2002), which was much lower than those encountered in the current study. Serum starvation may often result in reduced cell survival and increased DNA fragmentation, which in turn cause subsequent high embryonic loss after nuclear transfer (Shi et al, 2007).…”
Section: Discussioncontrasting
confidence: 72%
“…In the current experiment, birth weight of the cloned calf was at the higher end of the normal range (mean value, 26.68; range 15 to 41 kg), as established by Thevarnanoharan et al (2001). This is significant in light of previous studies on cattle, which found a 47% rate of large offspring syndrome in calves derived from the skin, ear or liver donor cells (Heyman et al, 2002). At present, at 2 years and 4 months of age (Supplementary Figure S6), the cloned calf exhibits normal growth and development (Supplementary Figure S7; unpublished data) and appears healthy.…”
Section: Discussionmentioning
confidence: 53%
“…These could lead to the onset of pathologies later in life as the result of very minor changes in chromatin structure and/or gene expression. Moreover, the altered foetal and placental growth that is well documented in bovine clones (Hill et al, 1999;Heyman et al, 2002;Constant et al, 2006) may also induce metabolic diseases in adulthood as a result of the foetal growth disturbance, as shown both in epidemiological studies in human and experimental work in animals (Barker and Clark, 1997;McEvoy et al, 2001;Gluckman and Hanson, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, somatic cloning in cattle is associated with a high incidence of miscarriage and perinatal death compared with cattle born from conventional reproduction methods like artificial insemination (AI) (Heyman et al, 2002), but past the neonatal period most clones develop into adults with apparently normal physiology and capacity to produce offspring (Lanza et al, 2001;Chavatte-Palmer et al, 2004;Wells et al, 2004). Furthermore, somatic cloning generates animals that carry the nuclear genome of the donor cell.…”
Section: Introductionmentioning
confidence: 99%
“…The poor outcome of SCNT seems to reflect the epigenetic status of differentiated donor nuclei which differ from the state of the reprogrammed chromatin in the functional gamete (reviewed by RIDEOUT et al 2001;EGLI et al 2008). Successful cloning therefore requires reprogramming of the donor chromatin in the recipient oocyte cytoplasm (HEYMAN et al 2002;HIIRAGI & SOLTER 2005). This raises the question of whether reprogramming of the germ cell chromatin as well as successful reprogramming of the donor nucleus upon nuclear transfer may rely on similar epigenetic mechanisms.…”
mentioning
confidence: 99%